Analisa Pelanggaran Pemakaian Tenaga Listrik Pada Pelanggan Tegangan Menengah (20 kV) di PT. PLN (persero) UP3 Ternate - Hadi Sirad, Mochammad Apriyadi; Muhammad, Miftah; Baharuddin, Ali H (Department of Electrical Engineering, University of Patria Artha, 2021)
Theft of electricity is an activity that harms the country where PLN as a party that distributes electricity has unconsciously lost its main commodity without any reciprocity in the form of payments. To steal electricity is not as difficult as imagined by most people, only by attaching pln cables thieves can freely use electricity, especially if the thief knows the method used by PLN in detecting thieves will be careful in determining how much the shift in bills so as not to be sniffed. Violation of Class III P3 as many as 5 Pln Customer Customers Non-Customers get a Violation of Class IV P4 as much as 1 customer and follow-up bills given on violations of class P1 is a violation that affects the power limit fines given Rp. 59.400 violations of class P2 a violation that affects the energy limit fines given Rp. 2.372,020. violation of class P3 an offence that affects the power limit and is an offence affecting the energy limit the fine given Rp. 11.516,563. PLN Non-customer customers get a violation of class IV P4 fines given to the customer group as much as Rp. 5.348,206.